THE INFLUENCE OF CAPITAL STRUCTURE, COMPANY SIZE, AND ASSET GROWTH ON FINANCIAL PERFORMANCE IN STATE-OWNED ENTERPRISES (SOES) - Maulana Hidayatullah; Aida Nahar (STABILITY : Journal of Management and Business, 2025)
This study aims to examine whether capital structure, firm size, and asset growth influence financial performance in state-owned enterprises (SOEs). The population in this study consists of companies listed as SOEs. The sample size includes 34 respondents, selected using the purposive sampling method. The research employs a quantitative approach, utilizing secondary data sources. Data analysis is conducted using multiple linear regression analysis with SPSS version 26. The results indicate that capital structure has a negative and significant effect on financial performance, firm size has no effect on financial performance, while asset growth has a positive effect on financial performance.